2013
DOI: 10.4321/s1886-36552013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical inertia in type 2 diabetes: a retrospective analysis of pharmacist-managed diabetes care vs. usual medical care

Abstract: BackgroundEvidence suggests that patients with type 2 diabetes (T2DM) suffer from a high rate of “clinical inertia” or “recognition of the problem but failure to act.” ObjectiveThe aim of this study is to quantify the rate of clinical inertia between two models of care: Pharmacist-Managed Diabetes Clinic (PMDC) vs. Usual Medical Care (UMC).MethodsPatients in a university based medical clinic with type 2 diabetes (T2DM) were analyzed in this retrospective cohort study. Patients were exposed to either PMDC or UM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…The intensification of anti-diabetes therapies also depends on individual patient’s characteristics including age, co-morbidities, the risk of hypoglycaemia, and provider and patient’s preferences [ 13 ]. However, a high proportion of people with T2DM fail to reach the recommended glycaemic targets for a considerable period of time post diagnosis of diabetes (glycaemic burden) [ 17 21 ]. Among those with poor glycaemic control [HbA1c ≥7% (≥53 mmol/mol)], an overwhelmingly large proportion of people do not receive intensified treatment in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensification of anti-diabetes therapies also depends on individual patient’s characteristics including age, co-morbidities, the risk of hypoglycaemia, and provider and patient’s preferences [ 13 ]. However, a high proportion of people with T2DM fail to reach the recommended glycaemic targets for a considerable period of time post diagnosis of diabetes (glycaemic burden) [ 17 21 ]. Among those with poor glycaemic control [HbA1c ≥7% (≥53 mmol/mol)], an overwhelmingly large proportion of people do not receive intensified treatment in time.…”
Section: Introductionmentioning
confidence: 99%
“…Among those with poor glycaemic control [HbA1c ≥7% (≥53 mmol/mol)], an overwhelmingly large proportion of people do not receive intensified treatment in time. This “delay in treatment intensification”, also termed as clinical inertia , has been discussed by some studies [ 17 21 ]. A recent study based on 80,000 patients with T2DM from the United Kingdom primary care system reported that the average time to intensification to two oral anti-diabetes drugs (OADs) from one OAD among patients with HbA1c above 7% (53 mmol/mol) was about 3 years [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients whose treatment is not intensified as recommended, and thus remain in poor glycemic control, are at a greater risk of long-term diabetes-related complications, such as retinopathy and nephropathy [ 5 , 6 ]. Several studies have demonstrated that patients with T2D frequently do not reach glycemic target and their treatment intensification is often delayed, both in terms of initiating insulin and later intensifying insulin regimens–this is known as clinical inertia [ 7 10 ]. Clinical inertia is a global issue that has shown little improvement in prevalence over the last decade [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only half of the patients with diabetes achieve a glycated hemoglobin A 1c (HbA 1c ) of less than 7% (1), despite the availability of effective antidiabetic therapy and clinical practice guidelines that are updated annually (2). Timely achievement of an HbA 1c goal might have a beneficial effect on clinical outcomes, such as development of macrovascular and microvascular complications of type 2 diabetes (3). The aim of our study was to analyze the time to achieve an HbA 1c of less than 7% for a pharmacist-physician managed (PPM) cohort, as compared with a usual medical care (UMC) cohort of patients with type 2 diabetes.…”
Section: Objectivementioning
confidence: 99%